Adjacent Beams Resource Sharing to Serve Hot Spots : A Rate Splitting Approach - Tomás Ramírez; Carlos Mosquera; Màrius Caus; Adriano Pastore; Nader Alagha; Nele Noels (36th International Communications Satellite Systems Conference (ICSSC), 2018)
This work addresses the uneven traffic demand scenario in multi-beam satellite systems, in which a hot-spot beam is surrounded by cold beams. After partitioning the hotspot beam in different sectors, resource pulling from cold neighbouring beams is allowed following an aggressive frequency-reuse scheme. As a consequence, the level of the co-channel interference within the hot-spot beam increases. A scheme known as Non-Coherent Rate-Splitting (NCRS) is employed to cope with this interference, based on the exclusive use of magnitude channel state information at the transmitter (CSIT). The receiver complexity is increased with respect to full CSIT precoding schemes, which are considered for benchmarking purposes. Different NCRS strategies are analyzed and compared with several partial and full CSIT schemes. The proposed solution not only shows an improvement with respect to partial CSIT benchmarks, but also displays a competitive performance against full CSIT precoders.